Railway transport in Tanzania: A critical analysis on its legal and regulatory framework - Kazi, Abdon David (Mzumbe University, 2023)
Dissertation Submitted in Partial Fulfillment of the Requirements for Award of the Masters Degree in Commercial Law (LL.M) of Mzumbe University